Recent advancement for improving gas production rate from perforated clusters in fractured shale gas reservoir - JIANG Shu,LI Yuanping,DU Fengshuang,XUE Gang,ZHANG Peixian,CHEN Guohui,WANG Hu,YU Ruyang,ZHANG Ren (Youqicang pingjia yu kaifa)
Generally there exist a large number of ineffective perforation clusters in multistage hydraulic fracturing of horizontal wells of shale gas reservoirs. So improving the effectiveness of perforation and maintaining the long-term conductivity of fractures are the main challenges to increase production and reduce costs for shale gas horizontal wells. Based on previous research results, the main reasons for low production of perforation clusters include: ① Fracture does not initiate or propagate effectively due to mechanical heterogeneity of shale reservoir, stress shadow between fractures, or difference of perforation erosion rate; ② The distribution of proppant is non-uniform between clusters and in fractures due to the difference of perforation displacement distribution within the stage, weak sand suspension ability of low viscosity fracturing fluid, and fracture bending, inclination and roughness; ③ The fracture conductivity is lost due to the breakage and embedding of proppant, diagenesis, formation and migration of formation particles. In order to solve the above problems, the optimization and technical solutions to facilitate the balanced initiation of fractures, the uniform distribution of proppants, and the improvement of fracture conductivity are proposed. They include new-type limited entry fracturing technique, degradable temporary plugging diversion, optimization of perforation parameters and sand-adding sequence, high-speed channel fracturing, high viscosity friction reducers and new-type proppants, etc., which are expected to provide benchmark for improving the effectiveness of perforation cluster fracturing of horizontal wells.